Allocative Efficiency in Okra (Abelmoschus spp) Production in Ayamelum Local Government Area of Anambra State, Nigeria - S. I. Ume; J. C. Nweke; S. O. Ucha; E. O. Idahosa (Archives of Current Research International, 2018)
Okro is a very important vegetable fruit and is cultivated by small scale farmers in the South East and South West of Nigeria. Poor yield has characterized its production in recent times and this is evidenced by poverty that typifies the okra farmers. Studies attributed this scenario to poor resource use by the okra farmers. It is this problem that this study tends to address. 120 farmers were selected from the study area using multi stage random sampling technique. Data used were generated through structured questionnaire and interview schedule from the respondents. Net farm income analysis and ordinary least squares regression method were used to analyse the objectives of the study. Result shows that okra production in the study area was profitable with positive net farm income of ₦482,100. Result of the resource efficiency showed that farmers did not achieve optimum allocative efficiency in the use of the any of the resources such as fertilizer, seeds, and pesticides. The result of the elasticity of production revealed that the farmers were operating at increasing returns to scale. The study recommended on the need for policy options that would enable farmers to employ more of the resources that were underutilized, while for over utilized resources, farmers should use less of the resource in their productions in order to achieve higher productivity.